Comparison of middle-term valve durability between transcatheter aortic valve implantation and surgical aortic valve replacement: an updated systematic review and meta-analysis of RCTs - Lerman, Tsahi T.; Levi, Amos; Jørgensen, Troels Højsgaard; Søndergaard, Lars; Talmor-Barkan, Yeela; Kornowski, Ran (Frontiers in Cardiovascular Medicine, 2023)
Background: In this study we aimed to compare valve durability between TAVI and surgical aortic valve replacement (SAVR). Methods: We conducted a systematic review and meta-analysis using data from randomized controlled trials (RCTs). The primary outcome was structural valve deterioration (SVD). Secondary outcomes were bioprosthetic valve failure (BVF), reintervention, effective orifice area (EOA), mean pressure gradient (MG) and moderate-severe aortic regurgitation (AR; transvalvular and/or paravalvular). Results: Twenty-five publications from 7 RCTs totalling 7970 patients were included in the analysis with follow-up ranges 2-8 years. There was no significant difference between the two groups regarding SVD (OR 0.72 [95% CI; 0.25, 2.12]). There was a statistically significant higher risk of reintervention in the TAVI group compared with SAVR (OR 2.03 [95% CI; 1.34, 3.05]) as well as a moderate-severe AR (OR 6.54 [95% CI; 3.92, 10.91]). There was a trend towards lower mean pressure gradient in the TAVI group (MD -1.61 [95% CI -3.5, 0.28]) and significant higher EOA (MD 0.20 [95% CI; 0.08, 0.31]). Conclusions: Current data indicates that TAVI compared with SAVR provides a comparable risk of SVD with favourable hemodynamic profile. However, a higher risk of significant AR and reintervention was demonstrated.